Human-Centered AI and Digital Technologies in HR: Empowering Employees and Redesigning Work - Ahmad, Abd Rahman; Md Sapry, Hairul Rizad; Jameel, Alaa S (JBS Nexus, 2025)
Human resource (HR) practices are undergoing a fundamental transformation due to the swift adoption of digital technologies and artificial intelligence (AI). AI presents previously unheard-of opportunities to enhance productivity and tailor experiences throughout the employee lifecycle, from hiring and training to performance management and real-time feedback. However, there are also significant concerns regarding employee autonomy, equity, and welfare that arise from this change. This paper examines how AI is being increasingly incorporated into HR tasks, highlighting both the advantages and disadvantages of this approach. Based on theories of human-computer interaction, business ethics, and organisational behaviour, we investigate how algorithmic decision-making affects psychological safety, autonomy, and trust. Case studies from leading companies, such as those from Microsoft and Atlassian, provide empirical evidence of how AI can be applied to HR procedures to supplement human judgment rather than replace it. This paper advocates a human-centred AI model for human resources that prioritises ethical design, participatory development, transparency, and human oversight. The paper concludes with a research agenda and useful suggestions to ensure that the use of AI in HR advances corporate objectives and enhances employee empowerment.